Pengaruh Variabel Moneter terhadap Penyaluran Kredit Perbankan di Indonesia - Dimas Prayoga; Nurjannah Nurjannah; Iskandar Iskandar (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study examines the effects of the exchange rate, narrow money supply (M1), inflation, and interest rates on bank lending in Indonesia. Using annual secondary data for the period 2010-2024 obtained from the Central Bureau of Statistics (BPS), Bank Indonesia, and the One Data Trade Portal of the Ministry of Trade of the Republic of Indonesia, the study employs Ordinary Least Squares (OLS) multiple linear regression to analyze the empirical relationship between monetary variables and bank lending. The results indicate that the exchange rate and M1 have positive and significant effects on bank lending, while inflation has a negative but insignificant effect and interest rates have a positive but insignificant effect. Simultaneously, all independent variables significantly affect bank lending. The findings suggest that exchange rate movements and liquidity conditions play a more important role in explaining bank lending than inflation and interest rates during the observation period. These results highlight the importance of maintaining monetary stability and adequate liquidity to support the banking sector’s intermediation function and promote sustainable credit growth in Indonesia.